Forced Displacement and Mixed Migration in the Horn of Africa - World Bank Group; UNHCR (World Bank, Washington, DC and UNHCR, Geneva, 2015)
The Horn of Africa (HOA) covers Djibouti, Eritrea, Ethiopia, Kenya, Somalia, South Sudan, Sudan, and Uganda. Despite its rich endowment in human, social, and natural capital, the region is plagued by a complex history of weak governance, insecurity, increasing environmental degradation, entrenched poverty, and a range of persistent development challenges. Conflict remains endemic in the region. The complex cultural, social, and political nature of these conflicts is compounded by demographic shifts due both to population growth and the movement of people, as well as imbalanced service provision, inaccessibility, the growing threat of pandemic diseases, increasing conflicts over scarce natural resources, and harsh climatic conditions including frequent droughts and floods.